GREEN SYNTHESIS OF PLANT-MEDIATED METAL NANOPARTICLES: THE ROLE OF POLYPHENOLS - LATIF MS; ABBAS S; KORMIN F; MUSTAFA MK (Asian Journal of Pharmaceutical and Clinical Research, 2019)
The use of metal nanoparticles (MNPs) in various fields is increasing day-by-day leading to a genuine concern about the issues related to their environmental and biological safety. The major approaches for the synthesis of NPs include physical and chemical methods which are expensive and hazardous to health in addition to being toxic to the environment. This review highlights the potential of plant extracts to carry out the synthesis of MNPs with a special emphasis on the role of flavonoids in nanosynthesis. This green and clean approach have been actively utilized in recent years as an alternative to conventional hazardous approaches. It has proved as cost-effective, non-toxic, less time and labor consuming, efficient, and eco-friendly method for the synthesis of MNPs with specific biological actions. This review also focuses on the role of polyphenols, including the flavonoids as bioreductants of metal salts for the synthesis of NPs along with their biomedical applications. Various examples of the MNPs, along with their biological actions, have also been summarized.